Personalized Online Advertisements as A Means of Enhancing Purchase Intention:The Mediating Effect of Advertising Value - Felicia Juliana Haloho; Endang Parahyanti (PSIKODIMENSIA, 2020)
The high number of online shopping transactions and the rapid increase in internet users in Indonesia has encouraged many marketers to advertise their products online. The growth of online advertising can no longer be limited or dammed, so efforts to increase the effectiveness of online advertising is a big challenge for marketers. Personalized advertising is one of the innovations that aim to increase the effectiveness of online advertising. This study combines models of web advertising, traditional advertising, smartphone advertising, personalization, and advertising value to understand how the process of personalization in online advertising influences purchase intention. Based on the results of the integration, researchers hypothesize that the advertising value mediates the relationship between personalization of online advertising and purchase intention. This study involved 327 respondents consisting of internet users in Jabodetabek by distributing questionnaires online. Data were analyzed by regression analysis using SPSS 22.0. The results show that personalization significantly influences purchase intention, personalization is significantly related to advertising value, advertising value is significantly related to purchase intention and the relationship between personalization and purchase intention is fully mediated by advertising value.